Evaluation of the Implications of Cultural Globalisation on African Cultural Heritage - TUGHHEMBA, Terfa; TARI , Peter (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
A critical look at the contemporary society reveals apparent cultural diffusion as there is the fear of some cultures being annihilated or dominated by the stronger culture(s). This is most evident in language, dressing, music and dance or rather performing and non performing art, and even religion, etc. As a result, the very soul of the African identity is gradually losing its existence with the advent of globalisation. This paper examined the implications of the incursion of cultural globalisation on African cultural heritage. The study adopted qualitative research tools where data were derived from books, journal articles and the internet. The expository and analytical methods of data collection were used. The expository method presented cultural globalisation, some philosophers’ and scholars’ views on the concept of globalisation. The analytical method appraised the role cultural globalisation play on African cultural heritage and also, established the future of African cultural heritage in the age of globalisation from the eyes of a philosopher. The researcher found out that there have been positive and negative impacts of cultural globalisation on African cultural heritage. The paper therefore, recommended that, there is need for Africans to reconstruct their hitherto cherished values to make it relevant again while also retaining their Africanness. In other words, a hybrid of the more acceptable elements of both Western and African cultures should be adopted. Most importantly, recognising and inculcating the contributions of African cultural values and heritage in the mist of globalisation can lead to the development of African society.